COMPLIANCY AS A MEDICO-SOCIAL AND ETHIC PROBLEM OF PEDIATRICS - G. L. Mikirtichan; T. V. Kaurova; O. K. Ochkur ("Paediatrician" Publishers LLC, 2012)
The article represents the clinic-sociological analysis of the compliancy among pediatric patients and the estimation of various factors influence on the patients' and their surroundings' adherence to the treatment regimen. For the compliance assessment physicians, children with allergic dermatosis at the age of 13-18 years old (n =295) and their parents (n =270) were interrogated with the special questionnaires. Received data confirms that there is decrease in compliance among the pediatric patients and their patients. It is more significant in older girls than in boys.